Unraveling the Impact of Destabilizing Shoes on Balance Control and Fall Prevention in Older Adults: A Systematic Review - In-Ju Kim (Annals of Geriatric Medicine and Research)
Background Falls pose a significant risk to older adults, often leading to severe injury and disability. One potential contributing factor to falls is footwear, particularly shoes with destabilizing features. This systematic review assessed the effects of destabilizing shoes on stability control and fall prevention in older adults, highlighting their effectiveness in balance control and fall prevention, and the detailing the specific review methodology. Methods We thoroughly searched relevant databases and meticulously screened the identified studies based on predetermined inclusion and exclusion criteria. We then extracted data from 30 eligible studies with various study designs and shoe types and synthesized this information to assess the impact of destabilizing shoes on balance and gait measures, fall incidence, and other relevant outcomes. Results While certain types of destabilizing shoes may improve specific aspects of balance and proprioception, they can also adversely affect steadiness control and potentially increase the risk of falls if not appropriately used. Therefore, the use of destabilizing shoes should be carefully considered and tailored to individual needs, with proper guidance and training to minimize fall risk. Conclusion The findings of this review significantly inform footwear design and selection in older adults and emphasize the need for additional research. By synthesizing the available evidence, this review highlights the potential benefits and risks associated with destabilizing shoes and suggests the need for careful evaluation of their use on a case-by-case basis. This review serves as a basis for future guidelines on the use of destabilizing shoes in older adults with the aim of developing effective fall prevention interventions.